Analisis Generalisabilitas Multi Faset pada Instrumen Penalaran Matematika SMP - Shofan Fiangga; Yurizka Melia Sari (Jurnal Elemen, 2017)
The aims of this study is to determine the internal consistency or reliability coefficient of the developed mathematics reasoning instruments in Junior High School by using generalizability theory multi facet, px(i:r). The instrument are consisting 5 indicator which each of that are valued by each rater. This research method is three-way analysis of variance of multi facet design on G-Study by which the variance comonents are person, rater, item and the interaction between person and items, and the error. Both of G-Study and D-Study design is nested design. The result shows that the coefficient of G-Study is 0.66898. Hence, the next step is using those coefficient for D-Study analysis which lead the conclusion that mathematics reasoning instrument has satisfied the level of observation on large facet and its coefficient is 0.73834 or 74%. To sum up, raters have to use the indicators of reasoning instrument which consist of 1,2,3,4 and 5 components. The design of P x (I:R) - I Random, R Fixed (P = 30, R = 5 dan I = 4) has been satisfied the minimum criteria of conclusion which has been reach 0.70.